Potential Losses from Bootstrapping Activities Performed by Small and Medium Enterprise (SME’s) In Indonesia During The 2013-2019 Period - Solihin; Farhi Mohd Saudi, Hammad; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the potential losses due to bootstrapping activities carried out by small and medium enterprises (SME’s) in Indonesia since 2013-2018. Bootstrapping is an activity of running a new business using one’s own capital in a relatively small amount carried out by necessity entrepreneurs. What is meant by the necessity of entrepreneurs is entrepreneurs who choose self-employment because there are no other employment options. The research method used in this research is the descriptive research method. The data used to calculate potential losses due to the implementation of bootstrapping activities include data on the decrease in the number of SMEs performing bootstrapping and the average capital needed to start a new business. Data on the decrease in the number of SMEs performing bootstrapping was obtained using Total Early Stage Entrepreneurial Activity (TEA) data published by the Global Entrepreneurship Monitor (GEM). Based on TEA data, the estimated number of new entrepreneurs who stop doing business is 20,124,000 entrepreneurs. While the average capital spent by an entrepreneur to start a new business is obtained from GEM publications. The average capital spent by new entrepreneurs in bootstrapping is Rp4,866,925. Potential losses due to bootstrapping during the period 2013–2019 amounted to Rp97.94 trillion.